Food safety-related perspectives and practices of consumers and vendors in Ethiopia: A scoping review. (July 2022) - Parikh, Panam; Aparo, Nathaline Onek; Nordhagen, Stella; De Steur, Hans
Graphical abstract: Highlights: 116 relevant studies were identified through a well-defined search. Most studies focused on one state/city, urban areas, vendors, and practices. Studies suggest 'knowledge' and 'attitude' to be better than actual 'practices'. Food safety practices of consumers often aligned with those of vendors. Training may help improve knowledge, but rigorous evaluation is needed. Abstract: Despite being one of the first African countries to prioritize food safety, foodborne diseases are of acute concern in Ethiopia. This review aims to understand food safety-related perspectives and practices among consumers and food vendors in Ethiopia to identify motivations, beliefs, and values that shape and/or drive their practices. A well-defined search and review identified 116 relevant articles. These spanned eight of the ten regional states and two chartered cities, with most work focusing on urban areas and on a sample within one state or chartered city. Ninety-four studies focused on vendors or food handlers; fifteen articles examined both consumers and vendors, but only four assessed interactions between the groups. Meat, dairy products, and ready-to-eat (street) foods were the most studied food groups. Food service establishments were the most examined outlets. Forty-six studies examined generic food safety issues or concerns. Overall, 102 studies assessed food safety practices; 53 studies examined knowledge, and 19 studies assessed attitudes. A gap in vendors' observed practices versus knowledge and attitudes was noted. Consumer deductions of food safety were based on vendor practices. Both groups used physical attributes based on senses to assess quality and safety of animal-source foods, had their own 'coping' strategies to address food safety-related concerns, and had similar views on consumer choice motives. Analysis of food and the food handling environment revealed a high level of contamination. An additional study, included after the original search, identified training to be effective in influencing knowledge, attitudes, and practices – though results for attitudes and practices were not sustained in the long term. Future research should address consumers and consumer-vendor interactions and include the full triad of knowledge-attitudes-practices. It is also recommended to focus on nutrient-rich foods as well as on traditional markets and local eateries. Improving the quality of research will be critical to improve food safety in Ethiopia.